2011
DOI: 10.1080/14616734.2010.488122
|View full text |Cite
|
Sign up to set email alerts
|

Testing maternal depression and attachment style as moderators of early head start's effects on parenting

Abstract: This study examined maternal depression, attachment avoidance, and attachment anxiety as moderators of Early Head Start's effects on four parenting outcomes assessed at age 3. Participants (N = 947) were drawn from six sites of the Early Head Start National Research and Evaluation Project, a multi-site randomized trial. Findings suggest more positive program effects for mothers with less initial attachment avoidance or attachment anxiety. First, baseline attachment avoidance moderated EHS program effects on ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 42 publications
2
46
1
1
Order By: Relevance
“…The five prior observational studies revealed that parental attachment insecurity is associated with less sensitive and responsive parental behavior (Edelstein et al, 2004; Mills-Koonce et al, 2011; Selcuk et al, 2010), less supportive behavior (Berlin et al, 2011; Rholes et al, 1995), missing the child’s signals and interfering with exploration (Selcuk et al, 2010), and lower quality teaching behavior during a laboratory task (Rholes et al, 1995). However, the link between attachment style and observed parenting behavior appears to be more consistent for attachment-related avoidance than for attachment anxiety.…”
Section: Parental Attachment Style and Parenting Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…The five prior observational studies revealed that parental attachment insecurity is associated with less sensitive and responsive parental behavior (Edelstein et al, 2004; Mills-Koonce et al, 2011; Selcuk et al, 2010), less supportive behavior (Berlin et al, 2011; Rholes et al, 1995), missing the child’s signals and interfering with exploration (Selcuk et al, 2010), and lower quality teaching behavior during a laboratory task (Rholes et al, 1995). However, the link between attachment style and observed parenting behavior appears to be more consistent for attachment-related avoidance than for attachment anxiety.…”
Section: Parental Attachment Style and Parenting Behaviormentioning
confidence: 99%
“…However, relative to the substantial body of literature on adult attachment styles and romantic relationships, much less research has focused on parenting and parent-child relationships. Further, of the research that has focused on attachment styles and parenting, the vast majority has focused on self-reported thoughts, feelings, and behaviors related to parenting, with only five studies examining links between parents’ attachment styles and observed behavior in parent-child interactions (Berlin et al, 2011; Edelstein et al, 2004; Mills-Koonce et al, 2011; Rholes et al, 1995; Selcuk et al, 2010). It is also noteworthy that fathers were almost completely excluded from the five prior observational studies (Edelstein et al, 2004, included four fathers), and that these studies were limited to parents of children under the age of 7.…”
mentioning
confidence: 99%
“…Converging data from studies of infants, toddlers, and preschoolers indicate that mothers with higher levels of depressive symptoms or diagnosed depression are less positive, more negative, and less engaged with their children (Campbell, Cohn, & Meyers, 1995;Cummings & Davies, 1994;DeMulder & Radke-Yarrow, 1991;Field, 1992;Hops, Biglan, Sherman, Arthur, Friedman, & Osteen, 1987;Pelaez, Field, Pickens, & Hart, 2008;Teti & Gelfand, 1991). Maternal depression also has been shown to moderate the effects of interventions designed specifically to improve parent-toddler relationships and parenting style (Berlin, Whiteside-Mansell, Roggman, Green, Robinson, & Spieker, 2011).…”
Section: Attachment and Human Development 157mentioning
confidence: 97%
“…Studies have consistently shown that attachment-related avoidance is associated with less sensitive, responsive, and supportive parental behavior (Berlin et al, 2011; Edelstein et al, 2004; Goodman, Quas, Batterman-Faunce, Riddlesberger, & Kuhn, 1997; Mills-Koonce et al, 2011; Rholes, Simpson, & Blakely, 1995, Study 1; Selcuk et al, 2010). These studies revealed both main effects of avoidance on parenting behavior and interactions between avoidance and characteristics of the parent or child.…”
Section: Review and Analysis Of The Empirical Evidencementioning
confidence: 99%